Robbery Victimization in Early Adulthood, and Depression and Anxiety at Age 30 Years: Results From the 1982 Pelotas (Brazil) Birth Cohort Study - Orellana, Jesem Douglas Yamall; Murray, Joseph; Lima, Natália Peixoto; Pinheiro, Ricardo Tavares; Horta, Bernardo Lessa (Frontiers in Public Health, 2022)
Robbery is one of the most common urban crimes, but little is known about its relationship with mental disorders in young adults. This study aimed to assess the relationship between robbery victimization and Major Depressive Disorder (MDD), Generalized Anxiety Disorder (GAD) and comorbidity between MDD and GAD at 30 years of age. A birth cohort study has followed all children born in the city of Pelotas, southern Brazil, since 1982. At ages 23 and 30 years, participants were interviewed and asked about lifetime and recent experiences of robbery. Covariates were measured in interviews between birth and age 30 years. MDD and GAD were measured using the MINI-International Neuropsychiatric Interview. Adjusted prevalence ratio (aPR) and corresponding 95% confidence interval (CI) for associations between robbery and mental disorders were calculated using Poisson regression with robust standard error. Of 3,701 cohort members interviewed at age 30 years, 42% reported robbery victimization during their lifetime. Victimization across three periods (lifetime, past 10 years, past 12 months) was associated with increased occurrence of MDD, GAD, as well as the MDD and GAD comorbidity. The strongest associations were found to robbery occurring in the previous 12 months with the MDD and GAD comorbidity, both for burglary at home (aPR 2.52; 95% CI 1.52–4.22) or community family victimization (aPR 2.10; 95% CI 1.34–3.27). These findings highlight the importance of community violence for mental health in young adulthood, and the need for public policies to prevent violence as well as support services for victims to mitigate its adverse health consequences.